Changes of Morphological, Optical, and Electrical Properties Induced by Hydrogen Plasma on (0001) ZnO Surface. Issue 16 (21st August 2022) - Remes, Zdenek; Artemenko, Anna; Ukraintsev, Egor; Sharma, Dhananjay K.; Buryi, Maksym; Kromka, Alexander; Potocky, Stepan; Szabo, Ondrej; Kulicek, Jaroslav; Rezek, Bohuslav; Poruba, Ales; Micova, Julia; et al.
Abstract : Hydrogen Plasma Plasma provides specific adjustment of solid‐state surface properties offering an alternative to high temperature treatment. In article number 2100427, Zdenek Remes and co‐workers study the hydrogen plasma treatment of monocrystalline ZnO surface in an inductively coupled plasma reactor with reduced capacitively coupled plasma mode. The surface properties strongly depend on the electrical potential of the holder during plasma treatment.